Development of High-Strength Conductive Concrete Mix Using Locally Available Materials - Othman, Obida (2024)
A Master of Science thesis in Civil Engineering by Obida Othman entitled, “Development of High-Strength Conductive Concrete Mix Using Locally Available Materials”, submitted in January 2024. Thesis advisor is Dr. Sherif Yehia and thesis co-advisors are Dr. Nasser Qaddoumi and Dr. Mohamed Elchalakani. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).